Statutory Bodies and Other Attached Offices under the Ministry of Micro, Small and Medium Enterprise - Dr. H M Naveen, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The MSME sector has merged as a highly vibrant and dynamic sector in the Indian economy. It is fostering entrepreneurship and generating large employment opportunities. Further, it is widening its domain sectors by producing diverse range of products and services. M/o MSME is promoting growth and development of the Sector, including Khadi, Village and Coir Industries, in cooperation with the other concerned Ministries / Departments, State Governments and other Stakeholders by supporting the existing enterprises, using cutting edge technologies and encouraging creation of new enterprises. A number of statutory and non-statutory bodies work under the M/o of MSME include the Khadi and Village Industries Commission (KVIC), Coir Board, National Small Industries Cooperation (NSIC), National Institute for Micro, Small and Medium Enterprises (NIMSME), and Mahatma Gandhi Institute for Rural Industrialization (MGIRI). Details about the authorization and execution of these bodies are presented in this article.
Keywords: M/o MSME; KVIC; Coir Board; NSIC; NIMSME; MGIRI; MSME; entrepreneur-ship; Indian economy; Stakeholder; Statutory and Non-statutory Bodies